Pediatric management challenges of hyperglycemic hyperosmolar state: case series of Korean adolescents with type 2 diabetes - Sumin Lee; Sukdong Yoo; Ju Young Yoon; Chong Kun Cheon; Young A Kim (Korean Society of Pediatric Endocrinology, 2022)
The hyperglycemic hyperosmolar state (HHS) is considered the most fatal complication of type 2 diabetes mellitus (DM). The number of case reports describing pediatric HHS has increased recently in parallel with obesity and the prevalence of type 2 DM in pediatric patients. In this study, we investigated the patient characteristics and outcomes of HHS in 9 adolescents with obesity and type 2 DM. Almost all patients exhibited mixed clinical features of HHS and diabetic ketoacidosis (DKA), including characteristics such as hyperosmolality and ketoacidosis. These features made definitive diagnosis difficult; 5 out of 9 patients were initially diagnosed with DKA and were treated accordingly. Patients who were initially diagnosed with HHS received a more vigorous and appropriate fluid replacement than other patients did. No patients died, although 3 exhibited complications, such as arrhythmia, acute kidney injury requiring renal replacement therapy, rhabdomyolysis, and acute pancreatitis. Hyperosmolality with consequent severe dehydration is considered a significant factor contributing to the outcomes of patients with HHS. Therefore, early recognition of hyperosmolality is crucial for an appropriate diagnosis and adequate fluid rehydration to restore perfusion in the early period of treatment to improve patient outcomes for this rare but serious emerging condition in pediatric patients.